Delay in weight bearing in surgically treated tibial shaft fractures is associated with impaired healing: a cohort analysis of 166 tibial fractures - Houben, I. B. (Eur J Orthop Surg Traumatol, 2018)
BACKGROUND: The relation between timing of weight bearing after a fracture and the healing outcome is yet to be established, thereby limiting the implementation of a possibly beneficial effect for our patients. The current study was undertaken to determine the effect of timing of weight bearing after a surgically treated tibial shaft fracture. MATERIALS AND METHODS: Surgically treated diaphyseal tibial fractures were retrospectively studied between 2007 and 2015. The timing of initial weight bearing (IWB) was analysed as a predictor for impaired healing in a multivariate regression. RESULTS: Totally, 166 diaphyseal tibial fractures were included, 86 cases with impaired healing and 80 with normal healing. The mean age was 38.7 years (range 16–89). The mean time until IWB was significantly shorter in the normal fracture healing group (2.6 vs 7.4 weeks, p < 0.001). Correlation analysis yielded four possible confounders: infection requiring surgical intervention, fracture type, fasciotomy and open fractures. Logistic regression identified IWB as an independent predictor for impaired healing with an odds ratio of 1.13 per week delay (95% CI 1.03–1.25). CONCLUSIONS: Delay in initial weight bearing is independently associated with impaired fracture healing in surgically treated tibial shaft fractures. Unlike other factors such as fracture type or soft tissue condition, early resumption of weight bearing can be influenced by the treating physician and this factor therefore has a direct clinical relevance. This study indicates that early resumption of weight bearing should be the treatment goal in fracture fixation. LEVEL OF EVIDENCE: 3b.